KEMAMPUAN MENDESKRIPSIKAN MEDIA AUDIO VISUAL MENJADI TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 11 KOTA BENGKULU - Husnul Jayati; Suhartono Suhartono; Muhammad Arifin (Jurnal Korpus, 2020)
The purpose of this study was to describe the ability to write through audio-visual media into an explanatory text in class VIII students of SMP Negeri 11 Kota Bengkulu. The method used in this research is descriptive method with quantitative approach. This research was conducted at SMP Negeri 11 Kota Bengkulu. The technique used in this data collection is a test. Data analysis techniques used are descriptive analysis with a simple quantitative approach, data presentation, and conclusion drawing. The results showed that the ability to describe audio-visual media into explanatory text in class VIII students of SMP Negeri 11 Kota Bengkulu in general gained an average of 77,85 or the criteria for the ability to describe audio visual media into explanatory text in class VIII students of SMP Negeri 11 Kota Bengkulu was good. The ability to describe audio-visual media into explanatory text in class VIII students of SMP Negeri 11 Kota Bengkulu specifically from the content aspect gained an average of 17,9 with very good criteria, the sentence aspect gained an average of 24 with good criteria, the sentence aspect gained an average of 14,7 with good criteria, aspects of diction gained an average of 14,32 with good criteria, and spelling gained an average of 7,08 with good criteria.